A novel nanoparticle-based theranostic agent targeting LRP-1 enhances the efficacy of neoadjuvant radiotherapy in colorectal cancer. (October 2020) - Lee, Kyoung Jin; Ko, Eun Jung; Park, Yun-Yong; Park, Seok Soon; Ju, Eun Jin; Park, Jin; Shin, Seol Hwa; Suh, Young-Ah; Hong, Seung-Mo; Park, In Ja; Kim, Kyu-pyo; Hwang, Jung Jin; et al.
Abstract: Neoadjuvant radiotherapy has become an important therapeutic option for colorectal cancer (CRC) patients, whereas complete tumor response is observed only in 20–30% patients. Therefore, the development of diagnostic probe for radio-resistance is important to decide an optimal treatment timing and strategy for radiotherapy-resistant CRC patients. In this study, using the patient-derived xenograft (PDX) mouse model established with a radio-resistant CRC tumor tissue, we found low-density lipoprotein receptor-related protein-1 (LRP-1) as a radio-resistant marker protein induced by initial-dose radiation in radio-resistant CRC tumors. Simultaneously, we discovered a LRP-1 targeting peptide in a radio-resistant CRC PDX through in vivo peptide screening. We next engineered the theranostic agent made of human serum albumin nanoparticles (HSA NPs) containing 5-FU for chemo-radiotherapy and decorating LRP-1-targeting peptide for tumor localization, Cy7 fluorophore for diagnostic imaging. The nanoparticle-based theranostic agent accurately targeted the tumor designated by LRP-1 responding radiation and showed dramatically improved therapeutic efficacy in the radio-resistant PDX model. In conclusion, we have identified LRP-1 as a signature protein of radio-resistant CRC and successfully developed LRP-1-targeting HSA-NP containing 5-FU that is a novel theranostic tool for both diagnostic imaging and neoadjuvant therapy of CRC patients. This approach is clinically applicable to improve the effectiveness of neo-adjuvant radiotherapy and increase the ratio of complete tumor response in radio-resistant CRC.